Effect of Human Resources on the Competitiveness of African Companies (Global Journal of Human-Social Science, 2025)
The interest of the study is to make companies more competitive especially those in developing countries on an international scale The main objective is to study the link between the human resources of companies and their competitiveness in international markets Using SPSS software for data processing we arrive at the following results African companies employ much more women 99 2 than men 98 1 in their subsidiaries in international markets the results show that exports of goods and services of companies represent 98 1 of the Gross Domestic Product GDP of African countries exports of goods and services and primary income represent only 98 5 of the GDP of African countries
Keywords: effect; human resources; companies; competitive; international markets